Polymerase Chain Reaction for Biomedical Applications - Samadikuchaksaraei, Ali (IntechOpen, 2016)
Do you want to know the details that should be taken into consideration in order to have accurate conventional and real-time PCR results? If so, this book is for you. Polymerase Chain Reaction for Biomedical Applications is a collection of chapters for both novice and experienced scientists and technologists aiming to address obtaining an optimized real-time PCR result, simultaneous processing of a large number of samples and assays, performing PCR and RT-PCR on cell lysate without extraction of DNA or RNA, detecting false-positive PCR results, detecting organisms in viral and microbial diseases and hospital environment, following safety assessments of food products, and using PCR for introduction of mutations. This is a must-have book for any PCR laboratory.